Investigation of the Variation of Ocean Color and Phytoplankton Functional Types in the Bay of Bengal (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The monthly and inter annual variability of Ocean color products and Phytoplankton Functional Types (PFTs) are examined in the Bay of Bengal (BoB) from satellite data (2000-2020). Monthly Chlorophyll-a, Color Dissolved Organic Matter (CDOM), Photosynthetic Active Radiation (PAR) and Suspended Particulate Matter (SPM) data of merged satellites are used in this study. Ten PFTs (Microplankton, Nanoplankton, Picoplankton, Diatoms, Green Algae, Dinoflagellates, Prymnesiophytes, prokaryotes, pico-eukaryotes, Prochlorococcus; 3 phytoplankton size classes (PSC), 7 phytoplankton taxonomic compositions (PTC) are derived from individual monthly Chlorophyll-a. All data are averaged over the BoB region. We have found that the average Chlorophyll-a was decreasing (0.35 mg/m3 to .25 mg/m3) from the year of 2000 to 2020; whereas CDOM shows a sinusoidal relation from the year of 2000 to 2020; PAR has showed a decrease until 2014 then increase; SPM shows a rapid exponentially increasing trend from 2013. The highest Chlorophyll-a is found in the monsoon season (August) due to the high load of river discharge, cloudy environment, and associated favorable conditions; the lowest Chlorophyll-a is found in summer (April) due to the increased sunlight and PAR. Diatoms are the most dominant group in the BoB, which is going to be replaced by smaller planktons like Prochlorococcus species. Chlorophyll-a has a strong relationship with CDOM whereas PAR has a negative relationship with Chlorophyll-a and CDOM. Prokaryotes and Prochlorococcus have showed negative correlation with other functional groups.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 31-45